Upaya Meningkatkan Keterampilan Berbicara Kelas 2 Melalui Penerapan Model Role Playing SD Negeri 2 Tahunan - Natasya Arieni Fasya; Rifana Intan Fauziyah; Syailin Nichla Choirin Attalina (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research was conducted to find out about "speaking skills with role playing models". The purpose of this research was to find out the improvement of speaking skills by using the role playing model for students in grade 2 SD Negeri 2 Tahun. The method used in this study is to use a direct approach to students. The data collection technique used was carried out using tests, observations, and questionnaires. The expectations to be achieved from this research are 1.) knowing the improvement of speaking skills by using the role playing model. 2.) to give grade 2 students confidence in speaking skills. 3.) provide direct experience to play roles in learning. Based on the analysis of research data, speaking skills are carried out through cycle 1 and cycle 2. It can be seen from the increase in each existing cycle, namely from cycle 1 of 56.2% and there is an increase from cycle II of 80.9% of the 2 cycles which means there is an increase of 25% from cycle I.